2021
DOI: 10.3389/fpsyg.2020.594949
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Weight Bias Internalization Scale for Mainland Chinese Children and Adolescents

Abstract: Weight stigma internalization among adolescents across weight categories leads to adverse psychological consequences. This study aims to adapt and validate a Chinese version of the Weight Bias Internalization Scale for Mainland Chinese children and adolescents(C-WBIS). A total of 464 individuals aged 9 to 15 years participated in the present study. Based on item response theory (IRT) and classical test theory (CTT), we selected the items for the C-WBIS and evaluated its reliability and validity. The item respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…A similar result was found with WBIS versions for adolescents with obesity seeking bariatric surgery [53]. Regarding WBIS-M versions, the German WBIS-C for children also removed item 1 [27], as did the Mainland Chinese version for children and adolescents [26]. In the Chinese version with children and adolescents from Hong Kong, item 1 was retained, although it showed a very low factor loading [25].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…A similar result was found with WBIS versions for adolescents with obesity seeking bariatric surgery [53]. Regarding WBIS-M versions, the German WBIS-C for children also removed item 1 [27], as did the Mainland Chinese version for children and adolescents [26]. In the Chinese version with children and adolescents from Hong Kong, item 1 was retained, although it showed a very low factor loading [25].…”
Section: Discussionsupporting
confidence: 70%
“…The mean WBIS-M score was slightly below the middle range. When compared with other versions of the WBIS-M, which used the original 1-7 range scores, our mean WBIS-M score was slighly lower than in versions focused on adults, including the original version [23,30], and similar to other versions with youth and adolescents [24,26]. Because WBI research has mainly focused on adults, and few studies have been developed with adolescents across different weight statuses, more studies are needed to confirm this trend.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…A previous study compared the WBIS and the Weight Self-Stigma Questionnaire and showed a higher reliability of the former [16]. The original version of the WBIS is in English, and it has been translated into several languages [17][18][19], including Asian languages [20]. However, a Japanese version of the WBIS has not yet been developed.In Japan, the government began a health checkup for abdominal obesity in 2008, but the prevalence of obesity has not decreased between 2009 and 2019, with approximately 30% in males and 20% in females [21].…”
mentioning
confidence: 99%